2006
DOI: 10.1074/jbc.m603191200
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Properties of Human Aminopeptidase A

Abstract: Aminopeptidase A (APA) is a type II membrane-bound protein implicated in the regulation of blood pressure in the brain renin-angiotensin system. In this study, a recombinant soluble form of APA was expressed in a baculovirus system, purified to homogeneity, and characterized. By using synthetic substrates, it was shown that although the enzyme has a rather broad substrate specificity in the absence of Ca 2؉ , the preferential release of acidic amino acid residues was observed in the presence of Ca 2؉ . Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…Although leupeptin (a serine protease inhibitor) and pepstatin (an asparatic protease inhibitor) suppressed sLaeverin/APQ activity significantly only at high concentration (1 mM), E64 (a cysteine protease inhibitor) and p-(4-amidinophenyl)methanesulfonyl fluoride (a serine protease inhibitor) had only small inhibitory effects at 1 mM. Taken together, these data revealed that Laeverin/APQ is indeed a novel M1 aminopeptidase having enzymatic properties characteristic to the M1 family (7,13,23,24).…”
Section: Production Of a Recombinant Human Laeverin/apq-tomentioning
confidence: 56%
See 3 more Smart Citations
“…Although leupeptin (a serine protease inhibitor) and pepstatin (an asparatic protease inhibitor) suppressed sLaeverin/APQ activity significantly only at high concentration (1 mM), E64 (a cysteine protease inhibitor) and p-(4-amidinophenyl)methanesulfonyl fluoride (a serine protease inhibitor) had only small inhibitory effects at 1 mM. Taken together, these data revealed that Laeverin/APQ is indeed a novel M1 aminopeptidase having enzymatic properties characteristic to the M1 family (7,13,23,24).…”
Section: Production Of a Recombinant Human Laeverin/apq-tomentioning
confidence: 56%
“…inhibitory effects on the enzymatic activity of sLaeverin/APQ, which is consistent with the other M1 aminopeptidases so far tested. In our previous work, Ca 2ϩ was shown to modulate the enzymatic activity of APA (24). However, no significant effect of Ca 2ϩ on the enzymatic activity of sLaeverin/APQ was observed up to 3 mM.…”
Section: Production Of a Recombinant Human Laeverin/apq-tomentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Q181D ERAP1, which showed different substrate specificity from the wild-type enzyme and cleaved basic amino acids preferentially, also had only a marginal effect (16); thus, the enzymatic activity of wild-type ERAP1 is required for the enhancement of phagocytosis. We then examined the effects of other M1 aminopeptidases, such as placental leucine aminopeptidase (P-LAP)/insulin-regulated aminopeptidase/oxytocinase, laeverin/aminopeptidase Q (APQ), and aminopeptidase A (APA), on the uptake of IgG-coated latex beads (17)(18)(19). Because these three enzymes are membrane-bound proteins, we prepared recombinant soluble forms for this purpose.…”
Section: Resultsmentioning
confidence: 99%